A comparative study on the efficacy and safety of the distal transradial access and conventional transradial access in primary percutaneous coronary intervention - Santhosh KS; Ravi M; Unni TG; Benjamin B; Cenchery PK (Journal of Medical and Scientific Research)
Introduction: Distal transradial access (dTRA) in anatomical snuff box has advantages over the conventional transradial access at wrist (wTRA). There is limited data of dTRA in primary Percutaneous Coronary Intervention (PCI). The objective was to study the efficacy and safety of dTRA as compared to wTRA in primary percutaneous coronary intervention.